Life on the line in contemporary manufacturing - Delbridge, Rick (Oxford University Press, 2000)
Much is stated and written about the new world of work, but how much do we know about the contemporary workplace? What influence have Japanese management techniques had on the way work is organized? Have the systems and mechanisms of control changed radically in recent years, or are they much the same as they have always been? Rick Delbridge sought an answer to these questions at first hand by working on the shop floor in a Japanese consumer electronics transplant and a European automotive components supplier in order to witness and experience life on the line in contemporary manufacturing. Not only does his book offer rich empirical data on the lived reality of work and a management practice that may share little in common with that found in the textbooks; he also raises a number of important issues about the best ways to understand the complex and changing nature of work